Application value of electrical impedance tomography in assessment of patients with brain injury - NING Yachan, YAN Bin, LIU Bo, WANG Chunmei (Jichu yixue yu linchuang, 2024)
Electrical impedance tomography (EIT) estimates the spatial distribution of tissue electrical properties by measuring the transfer impedance between surface electrodes. which has shown great potential in medical imaging, especially in the evaluation of brain injury patients. This review introduces the application of EIT in the evaluation of brain injury patients, including diagnosis and monitoring of stroke, cerebral edema, and epileptic foci. In stroke research, consecutive and real-time EIT monitoring may support early diagnosis of intracranial lesions, identification of stroke types, and improvement of prognosis. For cerebral edema, EIT can monitor intracranial pressure in real-time and evaluate the effectiveness of dehydration treatment. EIT is used for lesion localization and seizure monitoring. The review also summarizes the existing problems of EIT and technical challenges that may orient future research as well as clinical application.